STRATEGI BAWASLU KOTA SUKABUMI DALAM PENCEGAHAN PELANGGARAN PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2024 PADA TAHAPAN KAMPANYE - Nur, Tuah; Talitha, Salma; Nur’ashila, Salsabila; Firdaus, Mutya (JRPA - Journal of Regional Public Administration, 2025)
Regional head elections are an important instrument of local democracy that is fraught with challenges, especially during the campaign period, which is prone to violations. This study examines the strategies employed by the Election Supervisory Agency (Bawaslu) of Sukabumi City in its efforts to prevent violations during the 2024 simultaneous regional elections. A descriptive qualitative approach was used, with data collected through interviews, observation, and documentation. The analysis is based on four dimensions of strategy according to Iman Mulyana, namely objectives, resources, environment, and capabilities. The results of the study show that although various prevention efforts have been implemented, such as socialization of regulations, direct supervision, and inter-agency coordination, their effectiveness is still hampered by limited human resources, low public understanding, and the complexity of the local political environment. The phenomena of money politics and violations of the neutrality of the civil service remain dominant, indicating the need to strengthen technology-based strategies and increase public participation. The recommendations of this study emphasize the importance of collaboration among stakeholders, the use of digital monitoring systems, and more massive political education to strengthen election integrity. With adaptive and participatory strategies, monitoring is expected to be more effective in realizing clean, transparent, and accountable democracy.